Insufflation with Humidified and Heated Carbon Dioxide in Short-Term Laparoscopy: A Double-Blinded Randomized Controlled Trial. (28th January 2015) - Herrmann, Anja; De Wilde, Rudy Leon
Abstract : Background. We tested the hypothesis that warm-humidified carbon dioxide (CO2 ) insufflation would reduce postoperative pain and morphine requirement compared to cold-dry CO2 insufflation. Methods. A double-blinded, randomized, controlled trial was conducted to compare warm, humidified CO2 and cold-dry CO2 . Patients with benign uterine diseases were randomized to either treatment (n = 48 ) or control (n = 49 ) group during laparoscopically assisted vaginal hysterectomy. Primary endpoints of the study were rest pain, movement pain, shoulder-tip pain, and cough pain at 2, 4, 6, 24, and 48 hours postoperatively, measured by visual analogue scale. Secondary outcomes were morphine consumption, rejected boli, temperature change, recovery room stay, and length of hospital stay. Results. There were no significant differences in all baseline characteristics. Shoulder-tip pain at 6 h postoperatively was significantly reduced in the intervention group. Pain at rest, movement pain, and cough pain did not differ. Total morphine consumption and rejected boli at 24 h postoperatively were significantly higher in the control group. Temperature change, recovery room stay, and length of hospital were similar. Conclusions. Warm, humidified insufflation gas significantly reduces postoperative shoulder-tip pain as well as morphine demand. This trial is registered with Clinical Trial Registration Number   DRKS00003853 (German Clinical Trials Register (DRKS)).